2011
DOI: 10.1007/s00436-011-2333-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and distribution of Cryptosporidium and Giardia duodenalis in raw urban wastewater in Harbin, China

Abstract: Contamination of the water supply by protozoa often causes outbreaks of cryptosporidiosis and giardiasis. The goals of the present study was to investigate the level of Cryptosporidium and Giardia duodenalis in wastewater from wastewater treatment plants in Harbin, China, and to understand the endemic transmission characteristics of cryptosporidiosis and giardiasis. Forty-eight domestic wastewater specimens from the two wastewater treatment plants in Harbin City were collected from April 2009 to March 2010. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
4
12
0
2
Order By: Relevance
“…Similar results were obtained by other authors, who reported that the predominant species/assemblages of Cryptosporidium and Giardia found in raw wastewater in China belonged to C. hominis, C. andersoni and/or Giardia assemblages A and B Liu et al, 2011). However, C. andersoni, C. bovis and C. suis and Giardia assemblages A and E were the dominant species/assemblages in mainstream of the Yangtze River and backwater areas of tributaries in the TGR, as they were found in 90% (9/ 10) of the Cryptosporidium positive samples and 100% (7/7) of the Giardia positive samples detected by PCR (Table 5).…”
supporting
confidence: 93%
“…Similar results were obtained by other authors, who reported that the predominant species/assemblages of Cryptosporidium and Giardia found in raw wastewater in China belonged to C. hominis, C. andersoni and/or Giardia assemblages A and B Liu et al, 2011). However, C. andersoni, C. bovis and C. suis and Giardia assemblages A and E were the dominant species/assemblages in mainstream of the Yangtze River and backwater areas of tributaries in the TGR, as they were found in 90% (9/ 10) of the Cryptosporidium positive samples and 100% (7/7) of the Giardia positive samples detected by PCR (Table 5).…”
supporting
confidence: 93%
“…C. andersoni is also one of the main Cryptosporidium species found in contaminated water such as the Potomac River in the United States [41], the Huangpu River in Shanghai [42], and in the urban wastewater plants in Harbin [43]. It is reasonable to suggest that C. andersoni infected humans could shed C. andersoni oocysts into urban wastewater, thus further contaminating water supplies and resulting in anthroponotic transmission of C. andersoni .…”
Section: Discussionmentioning
confidence: 99%
“…In China, one study characterized Cryptosporidium spp., G. duodenalis, and E. bieneusi in raw wastewater samples from four cities using PCR-sequencing tools (5), whereas another genotyped and subtyped Cryptosporidium spp. and G. duodenalis in wastewater samples in another city using the same approach (6). The results of the two studies suggest that wastewater may contribute to environmental contamination of waterborne pathogens.…”
mentioning
confidence: 88%